2019
DOI: 10.18805/ijar.b-3608
|View full text |Cite
|
Sign up to set email alerts
|

Coprological analysis for estimating prevalence of gastrointestinal parasites in captive sloth bears (Melursus ursinus)

Abstract: The aim of the present study was to investigate the gastrointestinal parasitic infestations in captive bears maintained in Wildlife SOS, Bannerghatta Biological Park, Bengaluru. A total of 85 fecal samples were collected over a period of 12 months from apparently normal/healthy captive bears and examined. The fecal samples were analysed using sedimentation and floatation techniques followed by microscopic identification of parasitic eggs. It revealed the prevalence of 51 (60%) Hymenolepis diminuta, 20 (23.52%)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 12 publications
1
1
0
Order By: Relevance
“…Comparing the findings of the present study with those reported elsewhere (both in the wild and in captivity) for the same taxa, in the Sloth bear, we recorded a low prevalence of trichurids (4%) which is consistent with that reported from Bengaluru for this species under captive conditions ( Manjunatha et al, 2019 ), but contrasts with findings of Veeraselvam and coworkers (2013) who reported a moderate prevalence of 32% for captive individuals. With respect to the civets, although similar parasites (e.g.…”
Section: Discussionsupporting
confidence: 83%
“…Comparing the findings of the present study with those reported elsewhere (both in the wild and in captivity) for the same taxa, in the Sloth bear, we recorded a low prevalence of trichurids (4%) which is consistent with that reported from Bengaluru for this species under captive conditions ( Manjunatha et al, 2019 ), but contrasts with findings of Veeraselvam and coworkers (2013) who reported a moderate prevalence of 32% for captive individuals. With respect to the civets, although similar parasites (e.g.…”
Section: Discussionsupporting
confidence: 83%
“…However, gastrointestinal parasites are common in sloth bears. Routine monitoring and administering anthelmintic periodically with proper sanitary measures would reduce the parasitic infection (Manjunatha et al, 2018) [11] . Some of the feces were grey or brownish-black, whereas the consistency varied from mucoid to watery, revealed the animal was suffering from hepatitis and cholangiocarcinoma (Figure 2).…”
Section: Resultsmentioning
confidence: 99%